APPROACHES FOR OVERCOMING POOR ORAL BIOAVAILABILITY OF DRUGS: NANOARCHITECTURES IN FOCUS - RANJITH ANISHETTY; SHIVANI PURI; VARUN GARG; ANKIT KUMAR YADAV; AMIT MITTAL (International Journal of Pharma and Bio Sciences, 2015)
Poor solubility of new drugs and their low oral bioavailability have become a major challenge for the pharmaceutical industries and the agencies that regulate them. Moreover, enzymatic and metabolic instability of these drugs has overburdened the scientists working in these areas to think for a better approach to formulate these drugs using novel technologies. For the last fifteen years, the impact of nanotechnology has become more evident in the area of oral drug delivery. The present review discusses various nanoarchitectures like nanosuspensions, lipidic nanocarriers, self-emulsifying delivery systems, liquisolid compacts, polymeric micelles and inorganic nanoparticles respectively. It also illustrates the advantages and challenges associated with their efficient delivery. Nanosuspensions and self-emulsifying drug delivery systems have gained maximum interest in the pharmaceutical market because of their industrial feasibility during scale up, stability, ease of preparation and lesser toxicity.